Kebijakan Manajemen Dalam Praktik Membingkai Ulang Kurikulum Rumpun Bidang Ilmu Manajemen Pendidikan Dan Administrasi Pendidikan Pada Sektor Lembaga Pendidikan Dan Tenaga Kependidikan (Lptk) Di Indonesia - Radiana, Usman; Nur, Zseilla; Lestari, Iswahyuni; Kurniasih, Eis (Jurnal Pendidikan Indonesia, 2022)
Learning in Higher Education could run with good if management curriculum designed effective and efficient. In Indonesia, there are two management program name field education that is management education and administration education so that direction curriculum different describe diversity curriculum. Research objectives this is for get information about policy management in practice frame repeat curriculum clump field knowledge management education and administration education in the sector institution education and energy education (LPTK) in Indonesia. LPTK in question are Tanjungpura University, Bandung Indonesian Education University, Jakarta State University, Syarif Kasim State Islamic University Riau, and Malang State University. Study this use method descriptive with approach qualitative. Research type this is studies case. Collector the data with study and analysis document. Data analysis using shared steps in three part namely; data reduction, data display and conclusion / verification. The results of the study obtained information that there were a number of group eye lectures taught for example General Courses (MKU), Expertise Courses (MKK), Faculty MKK, Study Program MKK, Compulsory MKK and Free MKK . The required weight and total credits taken by students different between LPTKs in Education Management and Education Administration. The Curriculum Management System must meet the steps of instructional design, syllabus preparation and course planning. Start policy conducted of the existing curriculum structure. Results and impacts obtained considered successful and received very positive feedback from all users. Naturally In reframing this curriculum it is necessary consider the preparation of an operational design which includes the preparation of adequate infrastructure, funding, personnel, schedule, and understanding of the system by all involved users and educators.